2021
DOI: 10.1016/j.scitotenv.2020.142746
|View full text |Cite
|
Sign up to set email alerts
|

The novel SARS-CoV-2 pandemic: Possible environmental transmission, detection, persistence and fate during wastewater and water treatment

Abstract: The contagious SARS-CoV-2 virus responsible for COVID-19 disease has infected over 27 million people across the globe within a few months. While literature on SARS-CoV-2 indicates that its transmission may occur predominantly via aerosolization of virus-laden droplets, the possibility of alternate routes of transmission and reinfection through environmental factors require considerable scientific attention. This review aims to collate information on possible transmission routes of this virus, to ascertain its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 219 publications
2
56
0
7
Order By: Relevance
“…While the mucosal surface is likely the entry site for SARS-CoV-2, examination of other tissues has revealed that high levels of ACE2/TMPRSS2 co-expression are present in the enterocytes of the ileum and colon, and the gut may have higher expression of these receptors than the lung [ 30 , 31 ]. The observation that some COVID-19 patients have gastrointestinal distress prior to developing respiratory symptoms as well as during disease progression may suggest a fecal–oral route of transmission [ 95 , 96 ]; evidence supporting this has been recently reviewed [ 97 , 98 ]. Similarly, gastrointestinal infection/distress was previously observed for the closely related SARS and MERS coronaviruses [ 99 , 100 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the mucosal surface is likely the entry site for SARS-CoV-2, examination of other tissues has revealed that high levels of ACE2/TMPRSS2 co-expression are present in the enterocytes of the ileum and colon, and the gut may have higher expression of these receptors than the lung [ 30 , 31 ]. The observation that some COVID-19 patients have gastrointestinal distress prior to developing respiratory symptoms as well as during disease progression may suggest a fecal–oral route of transmission [ 95 , 96 ]; evidence supporting this has been recently reviewed [ 97 , 98 ]. Similarly, gastrointestinal infection/distress was previously observed for the closely related SARS and MERS coronaviruses [ 99 , 100 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sludge has been found to harbor envelop virus due to the hydrophobic nature of the virus and organic matter present in the sludge, thereby making the magnitude of the virus concentration higher than those found in wastewater. This hydrophobic interaction has been reported to be largely responsible for virus attachment to solid materials like sludge ( Mohapatra et al, 2020 ). Chin et al (2020) also reported the persistence of SARS-CoV-2 on smooth surfaces, be it artificial or treated, such as plastic and steel than the rough surfaces such as paper, cloth, or wood.…”
Section: Life Cycle and Persistence Of Sars-cov-2 In Water-food- Environment Interactionsmentioning
confidence: 99%
“…At low RH conditions, aerosols evaporate rapidly, droplet size decreases, and droplet virus particles can travel longer distances. 89 , 90 A recent study showed that due to high humidity, the SARS-CoV-2 virus might be rapidly inactivated due to the interaction of water with the lipid envelope. 91 Furthermore, at low RH, the nasal airway in humans dries out more so that the mucosal layer is less effective in trapping pathogens.…”
Section: Transmission Of Sars-cov-2mentioning
confidence: 99%